High‐Performance Solution‐Processed Small‐Molecule Solar Cells Based on a Dithienogermole‐Containing Molecular Donor. Issue 3 (7th October 2014) - Sun, Yanming; Seifter, Jason; Huo, Lijun; Yang, Yali; Hsu, Ben B. Y.; Zhou, Huiqiong; Sun, Xiaobo; Xiao, Steven; Jiang, Lei; Heeger, Alan J.
<x xml:space="preserve">Abstract</x> A novel dithienogermole‐containing a small‐molecule donor termed p‐DTG(FBTTh2)2 is synthesized and characterized, and its optical, thermal, and electrical properties are found to be comparable to its silicon analogue (p‐DTS(FBTTh2)2). Solar cells based on an active layer of p‐DTG(FBTTh2)2 and the fullerene PC70BM exhibit a power conversion efficiency of up to 6.9%, indicating that p‐DTG(FBTTh2)2 is an excellent small‐molecule donor. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>